(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article highlights the problems of improving the quality of physical education for students of the Kokand State Pedagogical Institute. Based on the results of his own pedagogical research, the author offers some recommendations of a methodological nature on the implementation of integrated modular learning technology in the educational process.